A cross-sectional study on relationship between body mass index and menstrual irregularity among rural women in Tamil Nadu - Ganesan, Dinesh Kumar; Krishnan, Gokul Kumar; Chitharaj, Rajan Rushender; Boopathirajan, Ramkumar (International Journal Of Community Medicine And Public Health, 2019)
Background: Menstruation is a normal physiological process and irregular menstrual pattern is a problem affecting the quality of life among women in the reproductive age group. Although many factors contribute to the irregularity in menstrual cycles this study was conducted to find out the relationship between the body mass index (BMI) and irregular menstrual pattern. Methods: A cross-sectional study was conducted in the rural health and training centre of SRM hospital between August and October 2018 by using a convenience sampling method and data was collected from 163 women in the reproductive age group and analysed to find out the relationship between the BMI and menstrual irregularity. Results: The mean age of the study participants was 31.29 (±8.32) years and their mean age at menarche was 12.59 (±1.86) years. Majority of the study participants belongs to lower middle class (25%), Hindus (85%) by religion, married (82%), homemakers (53%) belongs to nuclear family (45%) having education up to high school level (61%). Only 44% of the participants have their BMI within normal range and 8% are obese. Irregular menstrual pattern was present in 13% of the study participants. The association between the BMI and the irregular menstrual pattern was found to be significant with a p<0.05. Conclusions: A significant association between the BMI and the irregular menstrual pattern highlights the importance of adapting simple and effective lifestyle and behavioural modifications in the reduction of excess weight thereby leading to healthy reproductive life among women.